Nature and nurture in French social sciences, 1859-1914 and beyond - Staum, Martin S. (McGill-Queen's studies in the history of ideas, 2011)
Deals with the dilemmas of early French social scientists inclined to stress either heredity or environment, but forced to concede the influence of both.